New Harpirhynchinae Dubinin (Acariformes: Harpirhynchidae)—intracutaneous and feather-base parasites of birds - Bochkov, Andre V; Klompen, Hans (Zootaxa, 2014)
Seven new species of intracutaneous parasites of the subfamily Harpirhynchinae Dubinin (Acariformes: Cheyletoidea: Harpirhynchidae) are described: Anharpyrhynchus elizae sp. nov. from Cyanocitta cristata (type host), Cyanocitta stelleri (Passeriformes: Corvidae), and Colaptes auratus (Piciformes: Picidae) from the USA; Anharpyrhynchus apodus sp. nov. from Lichmera indistincta (type host) and Phylidonyris novaehollandiae (Passeriformes: Meliphagidae) from Australia; Anharpyrhynchus lukoschusi sp. nov. from Manorina flavigula (type host) and Certhionyx pectoralis (Passeriformes: Meliphagidae) from Australia; Fainharpirhynchus legatus sp. nov. from Legatus leucophaius (Passeriformes: Tyrannidae) from Trinidad and Tobago; Fainharpirhynchus mossi sp. nov. from Myiarchus crinitus (Passeriformes: Tyrannidae) from an unknown locality in North America; Perharpyrhynchus caprimulgus sp. nov. from Caprimulgus fossii (Caprimulgidae: Caprimulgiformes) from Mozambique; Perharpyrhynchus elseyornis sp. nov. from Elseyornis melanops (Charadriiformes: Charadriidae) from Australia. Keys to females of the genera Anharpyrhynchus, Fainharpirhynchus, and Perharpyrhynchus are provided and data on hosts and distributions of all known intracutaneous harpirhynchines are summarized. In addition, a new non-subcutaneous harpirhynchine is described: Trichorhynchiella myiarchus sp. nov. from feather bases of Myiarchus crinitus (Passeriformes: Tyrannidae) from an unknown locality in North America.